An Unknown Risk Factor for Sepsis in Very Low Birth Weight Preterms: ABO Blood Groups (BGaPS Study) - Cakir, Ufuk; Tayman, Cuneyt; Buyuktiryaki, Mehmet (American Journal of Perinatology, 2019)
Objective There is insufficient study of the association of blood groups with neonatal diseases. The aim of this study was to evaluate the blood groups associated with sepsis and blood groups in preterm infants.Study Design This retrospective study was conducted between January 1, 2010 and November 31, 2018 in the neonatal intensive care unit (NICU). This study was done in single-center tertiary NICU. Infants born at gestational age (GA) <32 weeks with birth weight (BW) <1,500 g were included in the study.Results A total of 2,548 infants were included. The culture-proven sepsis ratio (30.2%) was the lowest in the O blood group and the highest in the AB blood group (37.5%) (p = 0.045). Meningitis ratio (6.5%) was significantly higher, and hospital stay (64.1 ± 33.9 days) was significantly longer in B blood group (respectively, p = 0.005, p < 0.001). In the AB blood group, GA (27.68 ± 1.12 weeks) was the lowest and early onset sepsis (EOS) (40.1%) and mortality (28.9%) ratio were found to be statistically higher (p < 0.001 for all groups). The AB group was significantly related to higher frequency of EOS (odds ratio [OR] = 2.93, 95% confidence interval [CI] = 1.68–5.12, p = 0.000), in addition to mortality (OR = 1.1, 95% CI = 0.55–2.19, p = 0.001). The O group was found to be associated with lower risk of late onset sepsis (LOS) (OR = 1.67, 95% CI = 1.06–3.058, p = 0.003) according to the model with corrected risk factor including GA, BW, and time of hospitalization.Conclusion Our study was the first study showing a relationship between certain blood groups and EOS/LOS in premature infants as well as meningitis.
Keywords: blood groups; early onset sepsis; late onset sepsis; prematurity; neonatal sepsis; very low birth weight